California Elected Women's Association for Education and Research Governor's Meeting Agenda (1977)
This document outlines the agenda for the California Elected Women's Association meeting with Governor Jerry Brown on August 10, 1977. The day includes discussions with the Governor, Secretary of State March Fong Eu, senior staff, and state agency leaders, followed by lunch with women officials and legislative briefings from Assembly Speaker Leo McCarthy and Minority Leader Paul Priolo. The schedule also features separate Democratic and Republican caucuses and concludes with cocktails and dinner attended by women legislators.